Photochemical efficiency in Hevea brasiliensis under varying light and CO2 in two agroclimatically distinct locations - Alam B; Jacob J; Nair D B (2nd International Congress of Plant Physiology on Sustainable Plant Productivity under Changing Environment 8-12 January, 2003 New Delhi : Abstracts)
Two clones of Hevea brasiliensis, a species adapted to warm humid conditions were grown at two distinct agro-climatic regions, namely Mattupetty, a cool hill station in the Western Ghats and Kottayam in the warm plains of Kerala. We measured at the same time the gas exchange rates (A) and chlorophyll fluorescence emission from intact fully mature leaves of these plants at different light intensities and CO2 concentrations (Ca). Light saturated rates of A, maximum potential PSII quantum yield (dark adapted Fv/Fm) and apparent PSII quantum yield ( PSII) were markedly reduced during winter in plants grown at Mattupetty compared to those grown at Kottayam where there was no low temperature stress. Even during the relatively stress-free post monsoon these parameters including efficiency of excitation energy capture by open PSII reaction center (Fv/Fm) and coefficient of photochemical quenching (qP) remained slightly less in plants grown at Mattupetty than Kottayam, but they could be considerably improved when the leaves were measured at higher Ca indicating the stress-ameliorating effect of CO2. Elevated CO2 led to increased electron transport through PSII and greater flux of these electrons to carbon reduction and reduced flux for other processes including photorespiration. The inhibitions in the physiological parameters were reflected in poor growth of the two clones at Mattupetty compared to Kottayam. Out of the two clones, the photosynthetic parameters were maintained better in PB 235 than in RRII 105 and this was reflected in the better growth of the former in Mattupetty.
Keywords: Hevea brasiliensis; Photochemical efficiency